The Problem of Tradition and Modernity in the Thought of Mohammed Abed Al-Jabri - Jabir, Salah Mohsen (Thi Qar Arts Journal, 2024)
The problem of tradition and modernity is the central axis around which Arab thought revolves, encompassing the options of renaissance and progress, reform and renewal, modernity and contemporaneity. This issue has been a focal point since the famous phrase by the Lebanese writer and thinker Shakib Arslan (1869-1946) in one of his books titled "Why Did Muslims Lag Behind and Others Progress?" Moroccan thinker Mohammed Abed Al-Jabri (1935-2010) was not alone in this field; he was preceded by other intellectual projects such as Adonis’s "The Static and the Dynamic" and Hussein Mroueh’s (1919-1987) "Materialist Trends in Islamic Philosophy," among many others. These thinkers were equipped with modern methodologies to read and understand this heritage. Al-Jabri attempted to provide a critical reading of the heritage, exploring its origins and roots by utilizing the archaeological approach of French philosopher Michel Foucault (1926-1984) to uncover the structure governing Arab thought. This research is divided into five sections. The first section addresses the question of modernity and tradition in Arab thought and its connection to the questions of renaissance as an extension of it. The second section presents the prevailing readings of heritage, detailing the perspectives represented in Arab thought, including the Salafi, liberal, and Marxist readings, which Al-Jabri considers all to be Salafi readings with only theoretical differences. The third section discusses the tools employed for reading heritage and the methodological steps used by Al-Jabri, including structural analysis, historical analysis, and ideological critique. The fourth section is dedicated to the topic of connecting the reader with the text and the problem of continuity, as discussed by Al-Jabri in his book "We and the Heritage." The fifth section provides a quick critical review of Al-Jabri’s project, questioning whether his procedural steps and methodologies enabled him to achieve an objective reading.